va rog ,dau coroanaaaaaa
Anexe:
Răspunsuri la întrebare
Răspuns de
9
z1 • z2 = ( 1 - m + i ) • ( m + 1 -2mi ) =
z1 • z2= m + 1 - 2mi - m² - m + 2m²i + mi + i - 2mi²
i² = - 1
z1•z2= 1 - mi - m² + 2m²i + i + 2m =
z1 • z2 = - m² + 2m + 1 + i (2m² + 1 - m)
Re ( z1 • z2 ) = - m² + 2m + 1
Im ( z1 • z2 ) = 2m² + 1 - m
z1 • z2 pur imaginar → Re ( z1 • z2 ) = 0
- m² + 2m + 1 = 0 | • ( - 1 )
m² - 2m - 1 = 0
∆ = b² - 4ac = (-2)² - 4•1 • (-1) = 4 + 4 = 8
m1,2 = -b+-✓∆/2a = 2+-✓8/2•1
m = { 1 - ✓2 ; 1 + ✓ 2 }
Alte întrebări interesante
Informatică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă